2014
DOI: 10.1016/j.schres.2014.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Illness insight and neurophysiological error-processing deficits in schizophrenia

Abstract: Impaired illness insight in schizophrenia is associated with non-adherence and worse outcomes. Schizophrenia patients also exhibit error-monitoring deficits, which have been proposed to cause poor insight. To test this hypothesis, we examined whether schizophrenia patients' deficits in neurophysiological error-monitoring indices, the error-related negativity (ERN) and error positivity (Pe) event-related potential (ERP) amplitudes, are associated with impaired insight. ERPs were recorded in 18 schizophrenia pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…Nearly all prior studies indicate decreased ERN in patients versus healthy controls (e.g., Foti et al, 2012, Horan et al, 2012, Kansal et al, 2014, Morris et al, 2008 with no patientcontrol differences on Pe (Horan et al, 2012, Mathalon et al, 2002, Morris et al, 2008. Our results are also consistent with two prior studies showing intact FN accompanied by impaired ERN in relatively small samples of individuals with schizophrenia (Horan et al, 2012, Morris et al, 2011.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Nearly all prior studies indicate decreased ERN in patients versus healthy controls (e.g., Foti et al, 2012, Horan et al, 2012, Kansal et al, 2014, Morris et al, 2008 with no patientcontrol differences on Pe (Horan et al, 2012, Mathalon et al, 2002, Morris et al, 2008. Our results are also consistent with two prior studies showing intact FN accompanied by impaired ERN in relatively small samples of individuals with schizophrenia (Horan et al, 2012, Morris et al, 2011.…”
Section: Discussionsupporting
confidence: 92%
“…Although it is called feedback negativity, this difference wave may actually reflect a reward-related positivity that is absent or suppressed following nonrewards , Proudfit, 2015. Many studies have found blunted ERN in schizophrenia compared to controls across different types of tasks (e.g., Foti et al, 2012, Horan et al, 2012, Kansal et al, 2014, Morris et al, 2006. Further, patients typically demonstrate normal CRN and Pe (Alain et al, 2002, Horan et al, 2012, Mathalon et al, 2002, Morris et al, 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Other published studies continue to fail to find a link between insight and multiple facets of neurocognition in patients in varying phases of illness 47,51,133,134 .…”
Section: World Psychiatry 17:1 -February 2018mentioning
confidence: 99%
“…Event-related potential (ERP) studies of error processing in schizophrenia have focused on the error-related negativity (ERN), which occurs 0-100 ms following errors on speeded tasks (Falkenstein et al, 1991; Gehring et al, 1993) and reflects error-related activation of the anterior cingulate cortex (ACC) (Holroyd and Coles, 2002). Numerous studies have observed a blunted ERN in schizophrenia (Alain et al, 2002; Bates et al, 2002; Bates et al, 2004; Foti et al, 2012; Foti et al, 2013; Horan et al, 2012; Kansal et al, 2014; Kopp and Rist, 1999; Mathalon et al, 2002; Morris et al, 2006), which is related to poor executive function (Kim et al, 2006). A blunted ERN has also been observed in other psychotic disorders (Foti et al, 2012; Foti et al, 2013; Minzenberg et al, 2014), high-risk individuals (Laurens et al, 2010; Perez et al, 2012) and unaffected siblings (Simmonite et al, 2012).…”
Section: Introductionmentioning
confidence: 99%